THE ROLE OF PERCEIVED SOCIAL SUPPORT IN MEDIATING THE RELATIONSHIP BETWEEN COVID-19 ANXIETY AND PSYCHOLOGICAL DISTRESS AMONG MEDICAL FRONTLINERS - Reyes, Ana Maria (International Journal of Allied Research in Sociology and Anthropology, 2024)
The COVID-19 pandemic has had far-reaching implications for the Philippines, impacting the economy, physical health, and mental wellbeing. With a significant number of infections and fatalities, anxiety has become pervasive among patients, frontline workers, and the general population. Healthcare institutions, in particular, have become high-risk environments for exposure to the virus, leading to increased workloads and profound mental stress among medical professionals. This mental impact is not unique to the Philippines but has been observed in various countries during previous pandemics. As a result, there is an urgent need to address the psychological well-being of both healthcare workers and patients. This study explores the psychological distress and anxiety experienced by individuals in the Philippines during the COVID-19 pandemic, shedding light on the immediate psychological needs of patients and healthcare professionals.